2019
DOI: 10.31234/osf.io/kt7py
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic comparison of global children’s and adult songs supports a sensorimotor hypothesis for the origin of musical scales

Abstract: Music throughout the world varies greatly, yet some musical features like scale structure display striking cross-cultural similarities. Are there musical laws or biological constraints that underlie this diversity? The “vocal mistuning” hypothesis proposes that cross-cultural regularities in musical scales arise from imprecision in vocal tuning, while the integer-ratio hypothesis proposes that they arise from perceptual principles based on psychoacoustic consonance. In order to test these hypotheses, we conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…However, the fact that average vocal tunings were much less precise than instrumental tunings, that Oceanian music had restricted ranges without a clearly predominant perfect 5th, and separate data showing differences in scale tuning precision between children's and adult music [9] could be argued to provide support for the competing vocal mistuning hypothesis, which proposes a motor origin of scale structure [8]. A sensorimotor hypothesis that combines these two theories may provide a more powerful theory for explaining unity and diversity in the world's scales [8,9] 5. FUTURE WORK Currently, our analysis assumes octave equivalence by collapsing pitch histograms into pitch class histograms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the fact that average vocal tunings were much less precise than instrumental tunings, that Oceanian music had restricted ranges without a clearly predominant perfect 5th, and separate data showing differences in scale tuning precision between children's and adult music [9] could be argued to provide support for the competing vocal mistuning hypothesis, which proposes a motor origin of scale structure [8]. A sensorimotor hypothesis that combines these two theories may provide a more powerful theory for explaining unity and diversity in the world's scales [8,9] 5. FUTURE WORK Currently, our analysis assumes octave equivalence by collapsing pitch histograms into pitch class histograms.…”
Section: Discussionmentioning
confidence: 98%
“…Our goal was to address this lack of data by taking advantage of new algorithms for automatic scale tuning analysis [12]. Based on the integer ratio hypothesis and previous preliminary studies [3,4,9], we predicted that the simplest ratios such as the perfect 5 th (3:2) and perfect 4 th (4:3) would predominate cross-culturally.…”
Section: Introductionmentioning
confidence: 99%
“…When MIR methods succeed in capturing higher-level aspects, they are often based on Western theoretical models (e.g., 12-note equal-tempered scales) and trained on human ground-truth data from Western listeners, resulting in biases toward such musical systems (see the review of MIR limitations in De Valk et al, 2017). There is increasing interest in expanding MIR methods to apply to folk and non-Western music, but substantial challenges remain for the cross-cultural application of automated methods (van Kranenberg et al, 2007;Lartillot & Ayari, 2014;Mehr et al, 2019;Panteli, Benetos, & Dixon, 2018;Sato et al, 2019;Serra, 2014Serra, , 2017Six, Cornelis, & Leman, 2013). Because there is no single best system at present, it seems advisable to use multiple analyses of music and behavior, testing for convergent validity.…”
Section: Empirical Methods: Recommendationsmentioning
confidence: 99%
“…To summarize, neurophysiological studies investigating the processing of harmony in the auditory system ( Blood et al, 1999 ), have evidenced an ability to discriminate between consonance and dissonance as well as the faster and easier processing of consonant as compared to dissonant signals. Additionally, cross-cultural studies have revealed that major music traditions around the world tend to make specific use of many of the same harmonic intervals (e.g., Blacking, 1970 ; Brown & Jordania, 2013 ; Sato et al, 2019 ; though see also Athanasopoulos et al, 2021) and that the most frequently used intervals correspond to those considered more consonant by culturally-diverse listeners ( Bowling & Purves, 2015 ; Burns, 1999 ). Remarkably, archaeological evidence of bone flutes that are capable of sounding consonance suggest dating the discovery of consonance to earlier than the Greek civilization (∼8,000 BP from Zhang et al, 1999 ; ∼35,000 BP from Conard et al, 2009 ).…”
Section: Harmonic Soundsmentioning
confidence: 99%